Synthesis and Characterization of 4‐, 5‐, and 6‐Coordinate Tris(1‐ethyl‐4‐isopropylimidazolyl‐κN)phosphine Cobalt(II) Complexes. Issue 12 (20th March 2015) - Easley, Chanel R.; Li, Jia; Banerjee, Atanu; Panda, Manashi; Brennessel, William W.; Loloee, Reza; Colacio, Enrique; Chavez, Ferman A.
Abstract: The synthesis and characterization of [Co(T1Et4 i PrIP)X2 ] {T1Et4 i PrIP = tris(1‐ethyl‐4‐isopropylimidazolyl)phosphine; X = OTf – (1 ), Cl – (2 ), Br – (3 )} and [Co(T1Et4 i PrIP)(CH3 CN)3 ](OTf)2 (4 ) were investigated. In compounds1 and4, T1Et4 i PrIP binds in a tridentate fashion, whereas2 and3 feature bidentate ligation. Compound1 additionally coordinates two triflate ligands to complete a distorted square pyramidal geometry. Compound4 also binds three acetonitrile ligands to afford a distorted octahedral geometry. Compounds2 and3 exhibit a distorted tetrahedral geometry for which the ligands comprise two imidazole nitrogen atoms and two halides. Bidentate coordination by using a tris(imidazolyl)phosphine ligand is unprecedented. Compounds2 and3 can be derived from1 by the addition of either Cl – or Br – salts, respectively, whereas4 can be generated by dissolving1 in acetonitrile. DFT studies indicate that the HOMO–LUMO gaps of all compounds are comparable; however, steric factors stabilize the formation of2 and3 over1 in the presence of halide ligands. Abstract : [Co(T1Et4 i PrIP)X2 ] {T1Et4 i PrIP = tris(1‐ethyl‐4‐isopropylimidazolyl)phosphine; X = OTf – (1 ), Cl – (2 ), Br – (3 )}, and [Co(T1Et4 i PrIP)(CH3 CN)3 ](OTf)2 (4 ) are reported. Dissolution of1 in MeCN affords4 . Reaction of1 with Cl – or Br – yields2 or3, respectively. DFT studies indicate that1 has the largest HOMO–LUMO gap, which suggests that the formation of2 or3 from1 is primarily sterically driven.